THE COMPANY SIZE AND THE GROWTH SALES THE EFFECT ON THE COAL COMPANY'S PERFORMANCE ON THE INDONESIAN STOCK EXCHANGE - Hammad, Hammad; Ismaya, Sakti Brata; Supriyani, Mei; Yulianti, Sri; Nuraini, Ani; Sova, Maya; Fajar, Imam (International Journal of Multidisciplinary Research and Literature, 2023)
This research aims to determine the effect of company size and sales growth on performance. Company size is a reflection of management's success in increasing company assets. Sales growth illustrates the company's success in expanding the marketing of its products. Company performance reflects its success in managing its finances well, proxied by Return On Assets (ROA). The analysis used in this research is panel data regression using secondary data taken from the Indonesia Stock Exchange (BEI) website. The companies studied are coal sub-sector companies listed on the IDX during 2020-2022. This research is essential now when coal is experiencing a surge in demand after previously experiencing its lowest phase. Therefore, coal companies must be able to prepare their company performance well to maintain the sustainability of their company. The research results show that company size has an effect, while sales growth does not affect company performance. The coefficient of determination in this study was 68%, which shows the level of goodness of the model in explaining company performance. This research answers the challenges of fluctuations in the coal mining industry that may occur in the future and is a solution to the uncertainty of coal demand and supply in the world. Therefore, coal companies must be able to prepare their company performance well to maintain the sustainability of their company. The research results show that company size has an effect, while sales growth does not affect company performance. The coefficient of determination in this study was 68%, which shows the level of goodness of the model in explaining company performance. This research answers the challenges of fluctuations in the coal mining industry that may occur in the future and is a solution to the uncertainty of coal demand and supply in the world. Therefore, coal companies must be able to prepare their company performance well to maintain the sustainability of their company. The research results show that company size has an effect, while sales growth does not affect company performance. The coefficient of determination in this study was 68%, which shows the level of goodness of the model in explaining company performance. This research answers the challenges of fluctuations in the coal mining industry that may occur in the future and is a solution to the uncertainty of coal demand and supply in the world. The coefficient of determination in this study was 68%, which shows the level of goodness of the model in explaining company performance. This research answers the challenges of fluctuations in the coal mining industry that may occur in the future and is a solution to the uncertainty of coal demand and supply in the world. The coefficient of determination in this study was 68%, which shows the level of goodness of the model in explaining company performance. This research answers the challenges of fluctuations in the coal mining industry that may occur in the future and is a solution to the uncertainty of coal demand and supply in the world